2013
DOI: 10.2203/dose-response.13-005.doss
|View full text |Cite
|
Sign up to set email alerts
|

Linear No-Threshold Model vs. Radiation Hormesis

Abstract: ᮀ The atomic bomb survivor cancer mortality data have been used in the past to justify the use of the linear no-threshold (LNT) model for estimating the carcinogenic effects of low dose radiation. An analysis of the recently updated atomic bomb survivor cancer mortality dose-response data shows that the data no longer support the LNT model but are consistent with a radiation hormesis model when a correction is applied for a likely bias in the baseline cancer mortality rate. If the validity of the phenomenon of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 67 publications
(114 reference statements)
1
93
0
7
Order By: Relevance
“…This curvature arises due to the less than expected cancer rates for the dose range of 0.3-0.7 Gy (See text on p.238 of the publication (Ozasa et al, 2012)). It results in a non-linearity of dose response that cannot be explained using the LNT model but is consistent with the radiation hormesis model (Doss, 2013).…”
Section: Recent Data Negate Carcinogenic Concerns Regarding Low Dose supporting
confidence: 72%
See 1 more Smart Citation
“…This curvature arises due to the less than expected cancer rates for the dose range of 0.3-0.7 Gy (See text on p.238 of the publication (Ozasa et al, 2012)). It results in a non-linearity of dose response that cannot be explained using the LNT model but is consistent with the radiation hormesis model (Doss, 2013).…”
Section: Recent Data Negate Carcinogenic Concerns Regarding Low Dose supporting
confidence: 72%
“…An analysis of the reported cancer incidence among the residents of apartments in Taiwan who were subjected to LDR from contaminated building materials (Hwang et al, 2006;Hwang et al, 2008) has shown a reduced overall cancer incidence in the radiated cohort in comparison to an age-matched control group (Doss, 2013).…”
Section: Recent Data Negate Carcinogenic Concerns Regarding Low Dose mentioning
confidence: 99%
“…In the study of Hiroshima and Nagasaki survivors [22], it was concluded that zero dose is the best estimate for the dose threshold, thus validating the LNT. This conclusion is, however, regarded questionable as the analysis had a priori restricted the possible functional forms of the dose-response relationship, resulting in the conclusion on a zero dose threshold [5,26]. If a more generalized functional form was used, the conclusion would have been different, as the lower bounds of the 95% confidence intervals would have been below zero for low doses; more details are in [5].…”
Section: Discussion Around Dose and Dose Rate Effectiveness Factor (Dmentioning
confidence: 99%
“…This conclusion is, however, regarded questionable as the analysis had a priori restricted the possible functional forms of the dose-response relationship, resulting in the conclusion on a zero dose threshold [5,26]. If a more generalized functional form was used, the conclusion would have been different, as the lower bounds of the 95% confidence intervals would have been below zero for low doses; more details are in [5]. The artificial neural networks method was reported to have circumvented the limitation of [22] and demonstrated the presence of a threshold of excess relative risk in humans exposed to ionizing radiation [27].…”
Section: Discussion Around Dose and Dose Rate Effectiveness Factor (Dmentioning
confidence: 99%
See 1 more Smart Citation